Comparison of patellar anchor fixation graft and graft through patellar tunnel reconstruction of medial patellofemoral ligament in the treatment of recurrent patellar dislocation: A protocol for a meta-analysis of comparative studies. Issue 3 (20th January 2023) - Tian, Jian; Yang, Jingfan; Dong, Wei; Zhang, Xiaoyan; Liu, Weitong; Chen, Jiankun; Yin, Hong; Zhou, Xing; Yuan, Changfei; Li, Jinlei
Abstract : Background: Recurrent patellar dislocation (RPD) occurs in people who have their own patellofemoral dysplasia and who have not been properly treated after their first patellar dislocation. For RPD where conservative treatment is ineffective, medial patellofemoral ligament (MPFL) reconstruction is the first choice for surgical treatment, but there are various and controversial ways of MPFL reconstruction and fixation. Initially, more scholars adopted the patellar lateral tunneling (PT) approach to contain and stabilize the graft, but with the newer materials and techniques, some experts adopted the lateral patellar anchor fixation (AF) of the graft, which can avoid the collateral damage caused by the patellar lateral tunneling and can obtain the same definite efficacy. Therefore, a meta-analysis must be performed to provide evidence whether there is a difference between AF and PT reconstruction of the MPFL in the treatment of RPD. Methods: We will search, with no time restriction, without any restriction of language and status, the time from the establishment of the database to October 2022, on the following databases: PubMed (MEDLINE), Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science, Chinese National Knowledge Infrastructure (CNKI), Wanfang Data (WF), Chinese Scientific Journals Database (VIP), and Chinese databases SinoMed (CBM) electronic databases. The electronic database search will be supplemented by a manual search of the reference lists of included articles. We will apply the risk-of-bias tool of the Cochrane Collaboration for randomized controlled trials to assess the methodological quality. Risk-of-Bias Assessment Tool for Non-randomized Studies was used to evaluate the quality of comparative studies. Statistical analysis will be conducted using RevMan 5.4 software. Results: This systematic review and meta-analysis will evaluate the functional outcomes of the two fixation modalities, AF and PT, in reconstructing MPFL for RPD. Conclusion: The findings of this study will provide a basis for clinical judgment of whether there is a difference between the two forms of AF and PT reconstructed MPFL for RPD.